The paraflagellar rod of kinetoplastid parasites: from structure to components and function. - Portman, N; Gull, K (2010)
The role of the eukaryotic flagellum in cell motility is well established but its importance in many other aspects of cell biology, from cell signalling to developmental regulation, is becoming increasingly apparent. In addition to this diversity of function the core structure of the flagellum, which has been inherited from the earliest ancestor of all eukaryotes, is embellished with a range of extra-axonemal structures in many organisms. One of the best studied of these structures is the paraflagellar rod of kinetoplastid protozoa in which the morphological characteristics have been well defined and some of the major protein constituents have been identified. Here we discuss recent advances in the identification of further molecular components of the paraflagellar rod, how these impact on our understanding of its function and regulation and the implications for therapeutic intervention in a number of devastating human pathologies.